Evaluating user acceptance of the UnityHub web-based system in higher education: a descriptive analysis - Umar, Norazah; Ahmad, Nurhafizah; Othman, Jamal; Kadar, Rozita (UiTM Cawangan Perlis, 2025)
The transition to hybrid learning in Malaysian higher education created a need for centralized platforms that enhance academic communication and class management. UnityHub was introduced as a web-based system to simplify group registration and strengthen student–lecturer interaction. The purpose of this study was to assess students’ acceptance of UnityHub using the Technology Acceptance Model (TAM) and to examine both the overall level of acceptance and the relative strengths and weaknesses of its dimensions. A total of 90 students from Universiti Teknologi MARA, Penang Branch participated in the survey, which used a TAM-based questionnaire comprising 24 items. Data were analyzed using descriptive statistics, including mean scores and standard deviations. The findings show that satisfaction scored highest (mean = 4.16), followed by attitude (3.80) and ease of use (3.78). Perceived usefulness (3.71) and intention to use (3.72) were moderately high, while self-efficacy was lowest (3.42). Overall, UnityHub achieved strong acceptance for usability and efficiency, though improvements in academic integration and user confidence are needed. The study is limited to a single department sample; future research should involve multiple faculties and compare UnityHub with other platforms to enhance generalizability.